ON FORMING THE PROFESSIONS SPECIFICATIONS UNDER THE DEVELOPMENT OF A NEW QUALIFICATIONS SYSTEM - I. Blinov, Vladimir; Yu. Esenina, Ekaterina; A. Sazonov, Boris (Gênero & Direito, 2020)
Introduction. The article reveals the features of description of secondary vocational education (SVE) graduates’ qualifications. New approaches are proposed for describing the SVE graduates’ qualifications, which take into account the existing traditions and the new aspects related to the changes in the normative regulation of labor market. Objective. To develop the methodology of updating the specifications of manual workers’ occupations and majors of SVE, taking into account the existence of constantly filled up registers of vocational standards and qualifications. Research methodology and methods. Analysis of the retrospective transformations of “qualification” definitions, compared to modern conceptions of this term. Results. Recommendations are offered, which refer to the description of qualifications when forming the updated professions classification in SVE sphere. The recommendations take into account that, for several years to come, the normative documents and all-Russian classifiers will act, which regulate the existing qualifications system. At the same time, the new, currently forming, qualifications system cannot be ignored. In the article, three alternative approaches to the description for SVE graduates’ qualifications are offered for this difficult situation. To make the final decision, the results of this work are supposed to be discussed with representatives of educational community (educational and methodological associations of SVE) and employers (represented by Councils for professional qualifications). Scientific novelty. The proposed recommendations take into account the increasing influence of the new, currently forming Russian system of qualifications on the labor market. Practical significance. The proposed approaches will promote establishment of compliance between the qualification within the educational system and the qualification apparent for the labor market.